Counselling implications of teaching economics through service learning instructional strategy to enhance entrepreneurship skills (2018)
It is evident that Nigerian Government is making drastic and pronounced efforts at stemming the tide of unemployment via means such as change and innovation in the curriculum. However, it appears that there is no adequate instructional intervention to develop appropriate knowledge, attitudes and skills in learners for knowledge economy in the schools. Students are restricted to classroom instruction with little or no participation which has resulted in rote learning and memorisation and their attendant effects on learning outcomes. This paper, therefore, explored service learning instructional strategy that is outdoor and activity-based as a means of promoting entrepreneurship skills through effective teaching of economics for alleviating unemployment in Nigeria and its counselling implications. The following were also discussed in the paper: Economics, entrepreneurship, importance of an entrepreneur, characteristics of entrepreneur, economic view of unemployment, causes of unemployment, and counselling implications of effective teaching of economics for boosting entrepreneurship skills for alleviating unemployment. Some recommendations were made such as Economics teachers should employ service learning instructional strategy for effective teaching of Economics, universities should expose Economics students to service learning, and collaborate with industries; management is encouraged to organise on-the-job pedagogical training for Economics lecturers without a teaching qualification, and continuous professional development on innovative instructional strategies for all. Parents are counselled to encourage their ward(s) on the need to discover their entrepreneurial skills and make good use of them to be self-reliant, among others. All these will help to produce graduates that will be relevant beyond 21st century.